COVID-19 in Pediatrics. Clinical and Epidemiological description of patients assisted at the British Hospital in Montevideo, Uruguay from March 2020 to May 2021 (Archives of Pediatrics of Uruguay, 2022)
Introduction: on 3/13/2020, the first cases of SARS Cov-2 infection were detected in Uruguay. In 2021, cases increased steadily, negatively impacting the health system that was reorganized. The British Hospital (HB), a private health organization at tertiary level started to work in a coordinated way at its 3 levels of care. They created a specific team to help improve the monitoring of suspected/confirmed cases. It has 7,922 users under the age of 15.Objective: describe the evolution of COVID-19 cases in patients aged 0-15 years assisted at the HB between August 1st, 20 and May 31st, 2021, assessing demographic, clinical and epidemiological aspects.Material and methods: retrospective descriptive study. The longitudinal follow-up record of pediatric users with microbiologically confirmed COVID-19 was analyzed.Results: 370 patients were included (51.5% female and 48.5% male), distributed by age groups (6.5%
Keywords: COVID-19; Child; Uruguay; Epidemiology